IIR Digital Filter Design Based on Intelligent Computation - Xueli, Chen (2016 International Conference on Smart Grid and Electrical Automation (ICSGEA), 2016)
As a basic function unit of digital signal processing, digital filter design is the main subject of research in the field of digital signal processing, it is widely used in the field of communication, radar and so on. The traditional design method is difficult to satisfied high performance requirements of digital filter. A kind of simplified artificial fish swarm algorithm is introduced into optimize the design of digital filter. The effectiveness and practicability of the presented method are verified with simulation experiments. The designed IIR digital filter has little pass-band fluctuation, smaller stop-band and more attenuation. It means that that the proposed IIR digital filter design method based on simplified artificial fish swarm algorithm is effective.